Comparison of Ondansetron and Dexamethasone for Prophylaxis of Postoperative Nausea and Vomiting in Patients Undergoing Laparoscopic Surgeries: A Meta-Analysis of Randomized Controlled Trials - Souvik Maitra; Anirban Som; Dalim K. Baidya; Sulagna Bhattacharjee (Anesthesiology Research and Practice)
Background. Postoperative nausea and vomiting (PONV) is a significant complication after laparoscopic surgeries. Ondansetron and dexamethasone are most commonly used drugs for PONV prophylaxis. Comparisons of these two drugs have not been systematically reviewed till date. Methods. PubMed, PubMed Central, and CENTRAL databases were searched with the following words: “dexamethasone,” “ondansetron,” “laparoscopy,” and “PONV” to identify randomized trials that compared ondansetron and dexamethasone for PONV prophylaxis after laparoscopic surgeries. Results. Data of 592 patients from 7 RCTs have been included in this meta-analysis. Incidence of postoperative nausea at 4–6 h is significantly lower when dexamethasone was used instead of ondansetron (p=0.04; OR 0.49, 95% CI 0.24–0.98, M-H fixed). Incidence of nausea is similar at 24 hours (p=0.08, OR 0.71, 95% CI 0.48, 1.05; M-H fixed); vomiting is also similar at 4–6 h (p=0.43, OR 1.27, 95% CI 0.70–2.27; M-H fixed) and also at 24 h (p=0.46, OR 0.92, 95% CI 0.73, 1.16; M-H fixed). Conclusion. Dexamethasone is superior to ondansetron in preventing postoperative nausea after 4–6 h of laparoscopic surgeries. However, both the drugs are of equal efficacy in preventing postoperative vomiting up to 24 h after surgery. However, results should be interpreted with caution due to clinical heterogeneity in the included studies.